Fate of autologous and fresh-frozen allogeneic block bone grafts used for ridge augmentation. A CBCT-based analysis - Spin-Neto, Rubens [UNESP]; Stavropoulos, Andreas; Pereira, Luís Antônio Violin Dias; Marcantonio, Elcio [UNESP]; Wenzel, Ann (Wiley, 2013)
Objectives: To evaluate dimensional changes in autologous (AT) and fresh-frozen allogeneic (AL) block bone grafts 6 months after alveolar ridge augmentation. Material and methods: Twenty-six partially or totally edentulous patients treated either with fresh-frozen AL bone or AT bone onlay block grafts prior to implant placement (13 patients in each group), were included in this analysis. Patients received CBCT (i-CAT Classic) examinations prior to surgery and 14 days and 6 months after grafting. Differences in alveolar ridge area among the various observation times were evaluated by planimetric measurements on two-dimensional CBCT images of the grafted regions. Nineteen grafted blocks from each group were evaluated. Results: Significant increase in alveolar ridge dimensions, allowing implant placement, was obtained with both types of grafts 6 months after grafting; no significant differences in alveolar ridge area were observed between the groups at the various observation times. However, graft resorption in the AL group was significantly larger compared to that in the AT group at 6 months. Conclusions: Larger bone graft resorption was seen in patients treated with fresh-frozen AL bone than in those treated with AT bone 6 months following alveolar ridge augmentation. © 2011 John Wiley & Sons A/S.
Keywords: Autograft; Bone allograft; Bone resorption; CBCT; Ridge augmentation; Tomographic evaluation